2022
DOI: 10.3892/mmr.2022.12618
|View full text |Cite
|
Sign up to set email alerts
|

GATA6‑induced FN1 activation promotes the proliferation, invasion and migration of oral squamous cell carcinoma cells

Abstract: GATA binding protein 6 (GATA6) is a transcription factor involved in cell fate decision making and tissue morphogenesis and serves a significant role in the progression of a number of types of cancer. The present study aimed to investigate the role and mechanisms underlying the effects of GATA6 in oral squamous cell carcinoma (OSCC). The expression levels of GATA6 were determined in a number of OSCC cell lines and the expression of GATA6 was knocked down to evaluate its role in the proliferation, invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…29,30 More relevantly, GATA6 has been found to promote the malignant behaviors of OSCC cells by activating the transcription of fibronectin 1. 14 Gain-and loss-of functions studies then revealed that suppression of GATA6 suppressed the malignant behaviors of the OSCC cells, which were rescued by COL5A1 upregulation. The GATA6 upregulation granted the malignant phenotype to OSCC cells; however, the proliferation, migration, invasiveness, apoptosis resistance, tumorigenesis and pro-angiogenic activity of the cells were blocked by further LINC00173 overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 More relevantly, GATA6 has been found to promote the malignant behaviors of OSCC cells by activating the transcription of fibronectin 1. 14 Gain-and loss-of functions studies then revealed that suppression of GATA6 suppressed the malignant behaviors of the OSCC cells, which were rescued by COL5A1 upregulation. The GATA6 upregulation granted the malignant phenotype to OSCC cells; however, the proliferation, migration, invasiveness, apoptosis resistance, tumorigenesis and pro-angiogenic activity of the cells were blocked by further LINC00173 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…13 GATA6 has been found to promote the malignant behaviors of OSCC cells by activating transcription of fibronectin 1. 14 Therefore, we postulated that there might be a GATA6-COL5A1 in OSCC as well that drives the malignant progression, and LINC00173 may influence the interaction and thus affect the malignant properties of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GATA6 upregulation has been shown in several tumors in the past, including CRC [ 65 ], gastric cancer [ 66 ], and cholangiocarcinoma [ 67 ]. According to Zhai and Luo [ 8 ], OSCC cell lines (HN4, HN6, SCC9, and Cal27) overexpress GATA6 in comparison to human normal oral mucosal epithelial keratinocytes. Furthermore, GATA6 knockdown suppressed the colony formation, proliferation, migration, and invasion of cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is because many OSCC patients are often diagnosed in advanced stages. OSCC has remained one of the mortal malignancies worldwide, with a 5-year survival rate of approximately 50%, indicating that the prognosis of OSCC patients is poor [7][8][9][10][11][12]. Thus, illustrating the exact mechanisms and markers underlying the development of OSCC may elevate patient survival [8,10].…”
Section: Introductionmentioning
confidence: 99%